2011
DOI: 10.1128/aac.01598-10
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Lopinavir in HIV-Infected Adults Receiving Rifampin with Adjusted Doses of Lopinavir-Ritonavir Tablets

Abstract: Rifampin coadministration dramatically reduces plasma lopinavir (LPV) concentrations. In healthy volunteers, doubling the dose of a lopinavir-ritonavir (LPV/r) capsule formulation overcame this interaction, but a subsequent study of double doses of the tablet formulation was stopped early owing to hepatotoxicity. However, healthy-volunteer study findings may not apply to HIV-infected adults. We evaluated the steady-state pharmacokinetics of LPV in HIV-infected adults virologically suppressed on an LPV/r regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 17 publications
3
62
0
Order By: Relevance
“…We found the median lopinavir concentration was 8 μg/mL, which is higher than reported elsewhere [17,18], but comparable to the trough concentrations after observed doses in a study conducted by our group from the same community [19]. Lopinavir pharmacokinetics demonstrate considerable interindividual variability, which may affect treatment outcomes.…”
Section: Discussionsupporting
confidence: 77%
“…We found the median lopinavir concentration was 8 μg/mL, which is higher than reported elsewhere [17,18], but comparable to the trough concentrations after observed doses in a study conducted by our group from the same community [19]. Lopinavir pharmacokinetics demonstrate considerable interindividual variability, which may affect treatment outcomes.…”
Section: Discussionsupporting
confidence: 77%
“…However, implementation of ‘super-boosted’ LPV is not practical in many settings as it is complex to prescribe and administer, and ritonavir solution has a short shelf life, hence clinics frequently run out of stock. An alternative approach using double doses of LPV/r achieved adequate concentrations of LPV in adults given rifampicin concurrently [2,5], but results in trough concentrations of LPV below the minimum recommended concentration in the majority of young children [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Only one retrospective study showed that in patients using nonadjusted dosing of lopinavir/ritonavir with rifampicin (n = 23), 40 62% had undetectable HIV RNA and 17% had adverse events while 40% of patients on a recommended dose of lopinavir/ritonavir (n = 5) had to prematurely stop lopinavir/ritonavir due to adverse events. Recently, a report from a South African collaborative group (n = 21) 41 suggested doubling the dose of LPV/r so that the concentrations of lopinavir will be sufficient as well as tolerable, which resulted in having only two patients who developed asymptomatic hepatitis. ) with and without rifampicin.…”
Section: Discussionmentioning
confidence: 96%